Dual‐layer model predictive control‐based scheduling of integrated electricity‐hydrogen‐heat microgrid - Pengfei Han; Xiaoyuan Xu; Zheng Yan; Zhenfei Tan (IET Renewable Power Generation)
Abstract As a newly widely used energy source, hydrogen has not yet been integrated with other energies efficiently, leading to low energy efficiency and high operating costs. This paper develops a novel cooperation model to coordinate electricity, hydrogen, and district heating systems and reduce operating costs. First, the mathematical model of electricity, hydrogen, and district heating systems coupled by electrolysers is established, and the bidirectional heat exchange (BHE) between hydrogen production and district heating networks (DHNs) is proposed. Then, a dual‐layer model predictive control (DLMPC) method is proposed for the integrated electricity, hydrogen, and heating microgrid (IEHHM) scheduling. The upper layer aims to deal with the hourly power variation and determine the IEHHM operation schedules, and the lower layer revises the power of electrolysers and combined heat and power (CHP) plants to follow the real‐time power variation of renewable energy generations (REGs). Simulation results show that: (1) BHE improves the thermal dynamics of electrolysers and DHNs, enhancing operational flexibility; (2) The DLMPC method enables timely adjustments to the dispatch schedule, reducing operating costs by responding to multi‐time‐scale power variations from REGs.